Developed a knowledge base of risk factors for postoperative cognitive dysfunction: a retrospective database study - Na Tang; Jianchao Duan; Xingyun Liu; Peiyi Li; Xuechao Hao; Linzhong Zhang (Scientific Reports)
Abstract Postoperative cognitive dysfunction (POCD), a heterogeneous spectrum of surgery/anesthesia-associated neurocognitive impairments, represents a critical clinical challenge due to its associations with prolonged hospitalization, increased mortality, and accelerated long-term cognitive deterioration. The development of targeted perioperative management strategies fundamentally depends on systematic risk factor identification, though current research remains hampered by significant heterogeneity and incomplete evidence synthesis across observational studies. To address this knowledge gap, we constructed the first panoramic knowledge base integrating multidimensional POCD risk factors through systematic analysis of 2,837 PubMed-indexed clinical studies (1991-20 May 2024). Utilizing a rigorous protocol developed by a multidisciplinary expert panel, 860 distinct predictive risk factors were extracted following stringent inclusion criteria and manual curation. This knowledge synthesis framework enables hierarchical visualization of risk elements spanning demographic, clinical, anesthetic, surgical, and biomarker domains. Postoperative cognitive dysfunction knowledge base (POCDKB) is a retrospective database study that serves dual translational purposes: providing clinicians with evidence-based decision support for personalized perioperative treatment plans, and establishing standardized data parameters for future mechanistic investigations. Implemented as a dynamic platform: ( http://sysbio.org.cn/pocdkb/ ), the resource features continuous evidence updates and collaborative data-sharing infrastructure to advance POCD research and therapeutic innovation.